PENGARUH CAMPURANSUBSOIL ULTISOL DENGAN KOMPOS TKKS SEBAGAI MEDIA TANAMDANVOLUME PENYIRAMAN TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Nst, Rizk1 Alip Utama; Yulia, Arnis En; ', Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research aims to determine the interaction between subsoil mixture with compost TKKS and watering volume and determine the exact interaction to provide the best growth in oil palm seedlings in the main nursery. The reasearch was carried out for 5 months starting from october 2014 until february 2015. This reasearch was conducted in Greenhouse Agriculture Faculty University Of Riau Campus Bina Widya KM 12,5 Simpang Baru Tampan, Pekanbaru. This research was conducted experiments using completely randomized factorial design, which consisted of 2 factors with 3 replications. The first factor is a mixture of ultisol sub soil with compost TKKS (C) based on the volume that consists of 3 levels, were : C1 = (1:2), C2 = (1:1), C3 = (2:1), the second factor is the watering volume (A) consisting of 3 levels, were :A1= 2 liter,A2= 1,5 liter, A3= 1 liter. Thus there are 9 combined treatment and 27 units of trial and each experimental unit contained two plants so that overall there are 54 plans. Results of analysis of variance followed by Duncan’s New Multiple Range Test (DNMRT) at 5%. The results showed that the interaction of a mixture of ultisol sub soil with compost TKKS the ratio of 1:2 and watering volume of 1.5 liter/day give the best effect on all parameters abserved.   Keywords :Oil palm, compost tkks, ultisol sub soil, watering volume.